2018
DOI: 10.1016/j.plipres.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Properties, metabolism and roles of sulfogalactosylglycerolipid in male reproduction

Abstract: Sulfogalactosylglycerolipid (SGG, aka seminolipid) is selectively synthesized in high amounts in mammalian testicular germ cells (TGCs). SGG is an ordered lipid and directly involved in cell adhesion. SGG is indispensable for spermatogenesis, a process that greatly depends on interaction between Sertoli cells and TGCs. Spermatogenesis is disrupted in mice null for Cgt and Cst, encoding two enzymes essential for SGG biosynthesis. Sperm surface SGG also plays roles in fertilization. All of these results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 228 publications
(382 reference statements)
2
42
0
Order By: Relevance
“…Although GG is a precursor of SGG, the synthesis of SGG is already completed in the early phase of spermatogenesis. The presence of GG in mature intact sperm is therefore very unlikely . Our gp120‐lipid binding experiments indicated that gp120 interacted with a respectable affinity for SGG, and the computational modeling studies further supported this finding (Figures C and ).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Although GG is a precursor of SGG, the synthesis of SGG is already completed in the early phase of spermatogenesis. The presence of GG in mature intact sperm is therefore very unlikely . Our gp120‐lipid binding experiments indicated that gp120 interacted with a respectable affinity for SGG, and the computational modeling studies further supported this finding (Figures C and ).…”
Section: Discussionsupporting
confidence: 69%
“…Similar to GC, SGC is also a non‐canonical attachment receptor of HIV‐1 and the binding of GC, SGC, and SGG liposomes in solution to gp120 has been previously demonstrated . Since SGG is usually present selectively in male germ cells, its presence in Vk2/E6E7 cells is unusual. Nonetheless, as a structural analogue of SGC, SGG may also be a non‐canonical attachment receptor of HIV‐1 on Vk2/E6E7 cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Female stingrays are also assumed to store sperm for a prolonged period [46], like other cartilaginous fishes which can store sperm for a year and beyond [47,48]. In mammals, the sulfogalactosylglycerolipid, called seminolipid, is indispensable for spermatogenesis, sperm function, and fertilization (reviewed in [49]). Specifically, the involvement of seminolipid in the direct binding to the zona pellucida was suggested [50].…”
Section: Tandem Ms Experiments To Elucidate the Assignments Of Unknowmentioning
confidence: 99%
“…As is demonstrated in Figure 5C, PE ether lipids occur mostly as plasmalogens except for testis where we find equal amounts of 1-O-alkyl and 1-O-alk-1'-enyl PE species. In testis, seminolipid is formed which is a complex ether lipid without a vinyl ether bond and is required for male fertility and sperm maturation 31 . Remarkably, male PEDS knock-out mice are fertile 32 ,5 underlining the notion that no vinyl ether bond is required for seminolipid function.…”
Section: Discussionmentioning
confidence: 99%